Association between Framingham risk score and metabolic syndrome in elderly (Revista Brasileira de Ciências do Envelhecimento Humano, 2016)
Metabolic syndrome is a set of factors that can increase the mortality from cardiovascular disease. Thus, knowledge about the prevalence of MS in the elderly is important, since the risk factors tend to increase significantly with age. The aim of this study is analyze the prevalence of metabolic syndrome (MS) among elderly according to the IDF and NCEP criteria and determining its relation to Framingham Risk Score (FRS). Elderly people (60 years old or older) of both genders participated in the study. Volunteers signed a TCLE and were interviewed, as well as physical exams. The biochemical analyzis were performed on an automated analyzer LABTEST, LabMax 240 model with biochemical reagents Labtest brand. For the diagnosis of MS NCEP and IDF criteria were used and cardiovascular risk was estimated by calculating the FRS. Descriptive statistics were performed, chi-square test for ordinal variables and ANOVA or Student-t test for quantitative data. Multivariate analysis was performed by logistic regression (backward conditional method). Differences were considered statistically significant at p â‰¤ 0.05. The overall prevalence of MS found in the sample following the NCEP and IDF criteria was 55.8% and 60.8%, respectively. No associations were found between gender and diagnostic criteria. Individuals with high+moderate FRS had a higher risk of developing MS compared to those with low FRS. Logistic regression analysis showed an independent association of abdominal adiposity by the IDF criteria (OR 4.8, CI 1.0- 22.1; p = 0.04) and glycemia by NCEP criteria (OR 3.0, CI 1.1-8.4; p = 0.03) with moderate+high FRS. The prevalence of MS was high under both criteria, being more predominant in those patients with moderate+high FRS. Thus, the components of MS abdominal adiposity and glucose levels were associated with increased CRF, indicating that the control of these factors can be decisive in reducing cardiovascular risk in the elderly.